Shaping Leadership at ACSC: A Commandant’s Perspective on What ‘Right’ Looks Like - Khatri, Bhuwan (The Shivapuri Journal, 2026)
The Army Command and Staff College (ACSC) of the Nepali Army serves as the premier institution for mid-career professional military education, developing mid-level officers through an intensive year-long program. This paper examines ‘What Right Looks Like’ for an ACSC graduate, focusing on how the course bridges the gap between tactical competence and strategic understanding. In an increasingly complex security environment characterized by hybrid threats and gray zone challenges, ACSC aims to develop scholar practitioners capable of addressing security problems that extend beyond conventional military solutions. The paper highlights the transition of officers typically from Major to Lieutenant Colonel, from direct tactical leadership to organizational, operational, and advisory roles. Through structured planning processes such as the Tactical Planning Process (TPP), ACSC prepares officers to serve as critical contributors at brigade, division, and Army Headquarters levels. Emphasis is placed on critical thinking, ethical leadership, and the ability to translate complexity into clear and actionable guidance. A qualitative research design has been used with descriptive and analytical methods in this study to examine the various aspects related to the mid-level officers. The data were collected from primary sources from the mid-level officers and secondary data were collected from various doctrinal manuals, scholarly articles, SOPs, Acts and Regulations. The collected data were analyzed and examined through thematic analysis. The study further explores the academic and global orientation of ACSC, including its Master’s Degree Program and focus on multinational operations, particularly United Nations peacekeeping. Ultimately, ACSC produces officers characterized by intellectual agility, operational competence, and moral integrity, capable of meeting contemporary and future security challenges.